A LEGAL AWARENESS OF COPYRIGHT ON REGIONAL SONG CREATORS - Muchtar A H Labetubun (International Journal of Law Reconstruction, 2021)
Copyright as an exclusive right for the creator or copyright holder to carry out the results of his ideas or ideas in the form of specific information or certain. Basically, copyright is the right to copy, adapt or produce a work, copyright is possible for the right holder to limit the copying or in any form without the illegitimate permission of a work, it can be realized by registration copyright, in its application, of course, there are obstacles that exist in the enforcement of copyright law itself. One example is the lack of awareness in registration copyright of songs by the creator. The research objective was to determine and analyze the legal awareness of regional pop songwriters to register their copyright. The research method uses normative research through a conceptual approach and a statue approach. The results show that the composers of regional pop songs know the importance of recording copyright because it is in accordance with the mandate of Act No. 28 of 2014 concerning Copyright and has also participated in the socialization carried out by the Ministry of Law and Human Rights, but songwriters do not record their work. Some songwriters consider that the registration is of no use because, from an economic standpoint, they cannot profit or lose personally, besides that their aspirations have not been fully channeled by the related institutions they shelter in this case the Collective Management Institute. Therefore to decide on the sale of the song's copyrighted work rather than registering it to the Ministry of Law and Human Rights in the Field of Intellectual Property.